Penerimaan Penggunaan Aplikasi E-MIMAS Di Kalangan Pentadbir Kewangan Masjid: Kajian Penerokaan - Norman Hamdan; Asharaf Mohd Ramli; Abdullaah Jalil; Mohammad Aizuddin Abdul Aziz; Asmaddy Haris (The Al-Azhar Mosque Management Board Kolej Universiti Islam Antarabangsa Selangor, 2024)
Non-Indexed Publication